2014
DOI: 10.1097/wnp.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Isolated Epileptiform Discharges for a Favorable Therapeutic Response to Antiepileptic Drugs in Nonepileptic Psychiatric Patients

Abstract: The efficacy of antiepileptic drugs (AEDs) in treating behavioral symptoms in nonepileptic psychiatric patients with abnormal EEGs is currently unknown. Although isolated epileptiform discharges have been reported in many psychiatric conditions, they are most commonly observed in patients with aggression, panic, or autistic spectrum disorders. The literature search was guided by 3 criteria: (1) studies had patients who did not experience seizures, (2) patients had EEGs, and (3) an AED was administered. Most im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Finally, it is not known whether currently available seizure medications are effective in normalizing hyperexcitable brain tissue that has not yet become capable of inducing seizures. Scattered reports suggest that a few of these medications may have some efficacy in this regards but further research is needed to examine these efficacies, particularly in newly diagnosed ASD patients (Boutros et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is not known whether currently available seizure medications are effective in normalizing hyperexcitable brain tissue that has not yet become capable of inducing seizures. Scattered reports suggest that a few of these medications may have some efficacy in this regards but further research is needed to examine these efficacies, particularly in newly diagnosed ASD patients (Boutros et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While there were no clear correlation between the discharges and particular aberrant behaviors, epileptic discharges were significantly more frequent during periods when the child was left alone and decreased when the child interacted with others. We have recently proposed that IEDs may be reflective of some degree of cortical hyperexcitability (Boutros et al 2014); however, a strong link between IEDs in the absence of seizures and behavioral symptoms remains far from being well established (So 2010).…”
Section: Role Of Epileptic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is some evidence that antidepressant treatment augmentation with anti-epileptic drugs is effective in treatment resistant MDD [60,61], although data about the association of response and epileptiform discharges are lacking. As a further example, previous studies have demonstrated an association between paroxysmal EEG activity and panic attacks [for a review, see [62], [63]]. Patients with panic disorder and epileptiform EEG patterns have been found to clinically respond to anticonvulsants [64], thus suggesting that there could be a subgroup of psychiatric patients in whom paroxysmal/epileptiform EEG activity could be associated with their psychiatric complaints and for whom anticonvulsant treatment could be a choice for augmentation of treatment or as stand-alone treatment.…”
Section: Biomarkersmentioning
confidence: 99%
“…The most important unanswered question remains the value of detecting IED activity in a nonepileptic psychiatric patient in predicting favorable responses to anticonvulsant treatment. 2 Slowing of the EEG is also seriously underinvestigated in psychiatric patients. The extent of medical follow-up of abnormal screening EEGs secured from psychiatric patients, particularly those reporting slow-wave abnormalities as a single finding, varies widely.…”
Section: Introductionmentioning
confidence: 99%